Composite Laminates for Aerospace and Packaging Fields - Rameswara Reddy, Y. (Asian Review of Mechanical Engineering, 2023)
Composite materials have become increasingly popular and widely used in the present world due to their unique combination of properties that cannot be achieved by any single material. In the current study the mechanical properties of composite laminates (Jute, palm and banana fibers) were fabricated by varying groundnut husk and seashell powders quantities (5, 10, 15 and 20gms) in epoxy resin using hand layup technique. In according to the ASTM standards, a mixture of Epoxy (LY556) and Hardener (araldite) HY951 is used. The ratio of epoxy to hardener is 10:1. The material will be properly mixed for some time before being used to create laminates. Samples were fabricated with different compositions of jute, palm and banana fibers. Tensile, Compression properties of laminates were analyzed by testing composite laminates on universal testing machine. In this context the weight ratio of groundnut husk to seashell powder is 2:1. Analysis states that both the powders have impact on the mechanical properties of laminates. The impact of groundnut husk powder is slightly more on the laminates mechanical properties (tensile, compression) when related to seashell powder.